2013
DOI: 10.5489/cuaj.1545
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-like carcinoma of the renal pelvis: Pathological and therapeutic implications

Abstract: A 75-year-old woman presented with a presumed urothelial carcinoma of the right renal pelvis. A radical nephroureterectomy was carried out and histological analysis of the specimen revealed lymphoepithelioma-like carcinoma. This is the seventh reported case of this normally nasopharyngeal tumour found in the renal pelvis. These tumours have a distinct histological appearance comprising sheets of undifferentiated syncytial cells on a background of lymphoid stroma. We review the pathological features of lymphoep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In this report, we describe an exceedingly rare case of renal pelvic LELC with a distinct component of squamous cell carcinoma. Most cases of LELC of the urinary tract have been found in the urinary bladder and rare isolated cases have been reported in the urethra, ureter, and renal pelvis [ 2 ]. The renal pelvis is an extremely rare site for LELC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this report, we describe an exceedingly rare case of renal pelvic LELC with a distinct component of squamous cell carcinoma. Most cases of LELC of the urinary tract have been found in the urinary bladder and rare isolated cases have been reported in the urethra, ureter, and renal pelvis [ 2 ]. The renal pelvis is an extremely rare site for LELC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Modi et al [ 2 ] reported a case of LELC of the renal pelvis with aspects of pathological and therapeutic implications. They summarized the characteristics of the reported seven cases of LELC of the renal pelvis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zukerberg firstly reported 5 cases of bladder LELC in 1991 [8]. So far, 8 cases of kidney of LELC have been reported [7,[9][10][11][12][13][14][15], except one in the kidney, another seven cases in the renal pelvis. Reports with complete CT images at present in abroad are only three [10,13,16].…”
Section: Introductionmentioning
confidence: 99%